Pengaruh Strategi Pembelajaran Berbasis Masalah Pada Konsep Pokok Perubahan Lingkungan Terhadap Hasil Belajar Peserta Didik Kelas X Madrasah Aliyah Teladan Ujung Kubu - Evi Zahara; Syarifah Widya Ulfa; Lailatun Nur Kamalia Siregar (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This study aims to determine the effect of learning using problem-based learning strategies on student learning outcomes on environmental change material at Teladan Batu Bara Madrasah Aliyah. This research is a type of quantitative research with a quasi-experimental design selected by Nonequavalent pretest posttest control group design. The research population was class X IPA Madrasah Akiyah Exemplary and the sample of this study was Class X IPA 1 with a total of 35 students as the experimental class, and X IPA 2 with a total of 35 students as the control class. The instrument in this study was in the form of a test in the form of multiple choice questions of 30 items. Data analysis of student learning outcomes using the t-test formula, also with the help of SPSS version 25 data processing. Data analysis of student learning outcomes with the results of calculating the relative learning outcomes shows that the experimental class using problem-based learning strategies is higher than the control class. The prerequisite test proved that the data were normally distributed and homogeneous. The results of simple linear regression test calculations show sig < 0.005, 0.000 problems < 0.05, this means that there is an influence from the problem- based learning system on student learning outcomes. The conclusions in this study explain that there is an effect of using problem-based learning strategies on student learning outcomes.